2021
DOI: 10.1111/add.15535
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Canada's cannabis legalization on police‐reported crime among youth: early evidence

Abstract: Aims Canada's 2018 Cannabis Act allows youth (age 12-17 years) to possess up to 5 g of dried cannabis (or equivalent) for personal consumption/sharing. This study assessed whether the Cannabis Act was associated with changes in police-reported cannabis offences among youth in Canada. Design Time series model using national daily criminal incident data from January 1, 2015-December 31, 2018 from the Canadian Uniform Crime Reporting Survey (UCR-2). Seasonal autoregressive integrated moving average time series mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
0
19
0
3
Order By: Relevance
“…12 Cannabis legalization might support increased patterns of cannabis use in society through a number of potential mechanisms, such as decreased perceived harmfulness, increased cannabis availability, elimination of criminal penalties as a deterrent to using, and changes in social norms making cannabis use more socially acceptable. 13,14 Cannabis legalization may also lead to net societal benefits, such as decreased impacts of a cannabis-related burden on the justice system, 15 reductions in cannabis-related criminalization and stigma, regulated and quality-controlled access to cannabis products, and development of cannabis-related treatment protocols and harm reduction interventions. 16,17 In this context, we tentatively expected that cannabis legalization would increase the number of hazardous cannabis-use episodes leading to the experience of cannabis-related harms in the populations of Ontario and Alberta-a pattern which, in turn, would likely contribute to detectable increases in ED presentations for cannabis-induced psychosis and, perhaps, more persistent psychotic syndromes (i.e., schizophrenia and related conditions).…”
Section: Introductionmentioning
confidence: 99%
“…12 Cannabis legalization might support increased patterns of cannabis use in society through a number of potential mechanisms, such as decreased perceived harmfulness, increased cannabis availability, elimination of criminal penalties as a deterrent to using, and changes in social norms making cannabis use more socially acceptable. 13,14 Cannabis legalization may also lead to net societal benefits, such as decreased impacts of a cannabis-related burden on the justice system, 15 reductions in cannabis-related criminalization and stigma, regulated and quality-controlled access to cannabis products, and development of cannabis-related treatment protocols and harm reduction interventions. 16,17 In this context, we tentatively expected that cannabis legalization would increase the number of hazardous cannabis-use episodes leading to the experience of cannabis-related harms in the populations of Ontario and Alberta-a pattern which, in turn, would likely contribute to detectable increases in ED presentations for cannabis-induced psychosis and, perhaps, more persistent psychotic syndromes (i.e., schizophrenia and related conditions).…”
Section: Introductionmentioning
confidence: 99%
“…There were no significant changes found to be associated with cannabis legalization (2018) on ED visit for traffic injuries (2015–2019) in a time-series analysis of data focusing on all and youth-only drivers in the provinces of Alberta and Ontario. In Alberta, there were 52,752 traffic-injury presentations with an increase of 9.17 visits and 3265 presentations and a decrease of 0.66 visits among youth drivers; correspondingly in Ontario, there were 186,921 presentations/28.9 increase in all drivers and 4565 presentations/increase of 0.09 visits among youth drivers; all non-significant) (Callaghan et al, 2021a , 2021b ).…”
Section: Resultsmentioning
confidence: 99%
“…A more comprehensive assessment of key outcomes associated with legalization will require consideration of its social impacts. These, for example, include community safety, crime and social cost effects but also the extent to which the elimination of the criminal enforcement and penalties for personal cannabis use and their adverse consequences (e.g., criminal records, educational/employment barriers, social injustice) have impacted on the lives and social welfare of the 5–6 million cannabis users (Callaghan et al, 2021a , 2021b ; Fischer et al, 2020a , 2020b ; Lu et al, 2021 ). Such comprehensive evaluations have yet to be implemented, but may eventually conclude that legalization has been an overall more measured and socially beneficial option for cannabis control in Canada (French et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using data from the Canadian Uniform Crime Reporting Survey (UCR-2), a recent study found that implementation of the Cannabis Act was associated with a significant decrease in police-reported cannabis-related criminal offences among youth aged 12-17 years, an effect that was significant among both boys and girls. Importantly, no association was observed between the implementation of the Cannabis Act and property crimes or violent crimes among youth, providing preliminary evidence that cannabis legalization was not associated with overall increases in youth crimes (112). Data reported by the Canadian Centre for Justice Statistics similarly found a decrease of 36% in cannabis possession cases among youth (aged 12-17 years) from 2017 to 2018 (113).…”
Section: Impact Of Cannabis Legalization For Non-medical Purposes On ...mentioning
confidence: 93%